Directory of institutions &​ individuals active in environmental training at tertiary level in Asia &​ the Pacific (Network for Environmental Training at Tertiary Level in Asia and the Pacific, 1993)
Report of the second NETTLAP resources development workshop for education and training at tertiary level in environmental economics